Oxford handbook of political science - Goodin, Robert E.(ed.) (New York, 2009)
Drawing on the rich resources of the ten-volume series of The Oxford Handbooks of Political Science, this one-volume distillation provides a comprehensive overview of all the main branches of contemporary political science: political theory; political institutions; political behavior; comparative politics; international relations; political economy; law and politics; public policy; contextual political analysis; and political methodology. Sixty-seven of the top political scientists worldwide survey recent developments in those fields and provide penetrating introductions to exciting new fields of study. Following in the footsteps of the New Handbook of Political Science edited by Robert Goodin and Hans-Dieter Klingemann a decade before, this Oxford Handbook will become an indispensable guide to the scope and methods of political science as a whole. It will serve as the reference book of record for political scientists and for those following their work for years to come.
Keywords: Political science